RAT INTESTINAL MICROFLORA IN APPLYING AUTOCLAVED CAROTENED YEAST IN EXPERIMENTAL DYSBIOSIS - Kaminska, M.V.; Stefanyshyn, M.; Gural, S.V.; Lytvyn, V. (World of Medicine and Biology, 2014)
The results of investigations of autoclaved carotened yeast biomass on the rats intestine microbiocenosis under the experimental dysbiosis caused by the introduction of antibiotics were presented. It is shown that combined use of autoclaved carotened yeast and doxycycline level the negative impact of antibiotics on the microflora composition in rats colon and its alignment to the indices for intact animals.
Keywords: intestinal microflora; autoclaved carotened yeast; experimental dysbiosis